2023
DOI: 10.1002/cpz1.921
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Mouse Embryonic Fibroblasts (MEFs)

Rita Ferreira,
Nadine Hein

Abstract: Mouse embryonic fibroblasts (MEFs) are primary fibroblasts purified from mouse embryos at a defined time post‐fertilization. MEFs have versatile applications, including use as feeder cell layers or sources of untransformed primary cells for a variety of biological assays. MEFs are most commonly isolated between embryonic day (E)12.5 and E13.5 but can be isolated from embryos as early as E8.5 and as late as E15.5. The individual embryos are harvested by carefully removing uterine tissue, yolk sac, and placenta.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, the mouse ABSCs could not expand in this culture system, which suggested that the CR culture method might not be directly applied to the culture of mouse ABSCs, and it needs to be further improved and optimized. NIH/3T3, MEFs, and RbEFs are representative feeder cells [ 17 , 27 29 ]. Therefore, 3T3-CM, MEF-CM, and RbEF-CM were subsequently used for further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mouse ABSCs could not expand in this culture system, which suggested that the CR culture method might not be directly applied to the culture of mouse ABSCs, and it needs to be further improved and optimized. NIH/3T3, MEFs, and RbEFs are representative feeder cells [ 17 , 27 29 ]. Therefore, 3T3-CM, MEF-CM, and RbEF-CM were subsequently used for further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…NIH/3T3 mouse embryonic fibroblasts were purchased from the Guangzhou Jennio Biotech Co., Ltd. and cultured in Dulbecco’s modified Eagle’s medium (DMEM; Gibco) supplemented with 100 U/mL penicillin, 100 μg/mL streptomycin (Gibco), and 9% newborn calf serum (NBCS; Gibco). Primary mouse embryonic fibroblasts (MEFs) were isolated from CF-1 mice at 12.5 days of gestation, and primary rabbit embryonic fibroblasts (RbEFs) were isolated from 20 to 22 days pregnant New Zealand rabbits according to the previously described method [ 17 ]. MEFs and RbEFs were cultured in DMEM containing 10% fetal bovine serum (FBS; Gibco), 100 U/mL penicillin, and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%